Visible‐Light Photocatalysis: A Low‐Cost Metal‐Free Photocatalyst Based on Black Phosphorus (Adv. Sci. 1/2019). Issue 1 (9th January 2019) - Wen, Min; Wang, Jiahong; Tong, Ruifeng; Liu, Danni; Huang, Hao; Yu, Ying; Zhou, Zhang‐Kai; Chu, Paul K.; Yu, Xue‐Feng
Abstract : Using economical urea and red phosphorus as the only raw materials, a low‐cost black phosphorus/graphitic carbon nitride (BP/CN) heterostructure is prepared on a large scale by ball milling in article number1801321 by Xue‐Feng Yu and co‐workers. The metal‐free heterostructure acts as an efficient and stable photocatalyst for both hydrogen evolution and dye degradation.